2022
DOI: 10.15829/1560-4071-2022-5021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ticagrelor and clopidogrel on angiographic parameters according to diabetic status in patients with ST elevation myocardial infarction

Abstract: Aim. We aimed to compare post-interventional angiographic outcomes of ticagrelor versus clopidogrel according to glycosylated hemoglobin (HbA1c) levels in patients with ST-elevation myocardial infarction.Material and methods. The study included a total of 532 patients, with 334 receiving ticagrelor (62,8%) and 198 clopidogrel (37,2%). Diabetic status of the patients was assessed with HbA1c. TIMI flow grade and TIMI frame count were calculated and compared between two groups.Results. TIMI flow grade 3 was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In-hospital GRACE score > 140 is considered as increased risk of mortality. In addition, recent studies have proposed a variety of parameters to predict the outcomes of ACS patients [ 16 19 ]. In this study, we found that serum Cys-C level was correlated positively with GRACE score at admission and after discharge, indicating that serum Cys-C level may be used for early risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…In-hospital GRACE score > 140 is considered as increased risk of mortality. In addition, recent studies have proposed a variety of parameters to predict the outcomes of ACS patients [ 16 19 ]. In this study, we found that serum Cys-C level was correlated positively with GRACE score at admission and after discharge, indicating that serum Cys-C level may be used for early risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Aydınyılmaz et al. [ 37 ] found that ticagrelor was superior in terms of angiographic parameters regardless of diabetes, and clopidogrel efficiency was found to be lower than ticagrelor, especially in patients with no-reflow and higher HbA1c levels. Our study suggests that HbA1c can effectively predict the risk of MACCE in anemia patients with PCI.…”
Section: Risk Stratificationmentioning
confidence: 99%